Analisis Determinan Kinerja Aparatur Sipil Negara (ASN) Pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPM-PTSP) Bengkulu Tengah - Dani, Rahiman; Jaya, Pory Rusman; Aprianty, Henny; Purnawan, Heru (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka, 2025)
Every organization makes an effort to achieve progress and development. The most influential factor in achieving these goals is human resources. Human resources that can advance an organization are people who perform well and are very effective. The qualified tasks and characteristics to achieve optimal performance. If the main tasks and functions of the organization are not clear, then people will find it difficult to do their jobs well, and it will be difficult to achieve good results. In addition, performance determinant factors are very much needed, including productivity, responsiveness, and accountability to achieve good and optimal performance. The importance of main tasks functions and performance determinants to realize human resource performance in the organization encourages the author to research the main tasks functions and performance determinants of ASN (State Civil Apparatus) of the Investment and One-Stop Integrated Service Office (DPM-PTSP) of Central Bengkulu. The aim is to determine the implementation of the main tasks and functions of the ASN performance determinants who work in the organization. The reason for researching ASN is because based on observations, the main tasks and functions have not been implemented properly and the performance determinant factors in the aspects of productivity, responsiveness, and accountability are indicated as not being good. So it still needs to be proven through research. The author uses interviews as a source of information, namely ASN who work in the organization. The results of the study indicate that the main tasks and functions given to ASNs are mostly good or very good, although some things are not good, namely the availability of ASN that is not consistent with appropriate ASN training and the work results achieved by ASN have not met management standards.